In Vivo Reprogramming of Striatal NG2 Glia into Functional Neurons that Integrate into Local Host Circuitry - Torper, Olof (Cell Rep, 2015)
The possibility of directly converting non-neuronal cells into neurons in situ in the brain would open therapeutic avenues aimed at repairing the brain after injury or degenerative disease. We have developed an adeno-associated virus (AAV)-based reporter system that allows selective GFP labeling of reprogrammed neurons. In this system, GFP is turned on only in reprogrammed neurons where it is stable and maintained for long time periods, allowing for histological and functional characterization of mature neurons. When combined with a modified rabies virus-based trans-synaptic tracing methodology, the system allows mapping of 3D circuitry integration into local and distal brain regions and shows that the newly reprogrammed neurons are integrated into host brain.